Efeito in vitro do veneno do escorpião Tityus serrulatus na indução da polarização de macrófagos para o perfil M1 - SOUSA, Kelly Portela (2017)
Macrophage activation by natural products has been studied in development or resolution of several pathological conditions, as an immunomodulatory therapeutic possibility. Since Tityus serrulatus scorpion venom (vTs) showed potential to activate and modulate these phagocytes response, this study aimed to evaluate murine macrophages polarization after treatment with vTs. For this, RAW 264.7 lineage cells were stimulated with vTs (0.1; 1; 10 μg / mL) and / or LPS (10 μg / mL) for 24 and 48 hours. After these treatments, we evaluated Zymosan particles (10: 1) and Escherichia coli-GFP (10: 1) phagocytosis, nitric oxide (NO), hydrogen peroxide (H2O2) and Cytokines (IL-6, TNF-α, MCP-1 and IL-12) production, and immunophenotypic characterization (CD80, CD86 and iNOS). Treatment with vTs was increased RAW cells phagocytic potential to Zymosan and E. coli. Although RAW cells increased microbicidal activity, vTs, alone, treatment did not induce NO production. However, groups stimulated with vTs plus LPS showed increased NO. Different from NO generation, all groups treated with vTs showed a stimulation of H2O2 production. The venom induced proinflammatory cytokines production, showing higher release of TNF-α and MCP-1. RAW cells stimulated with venom, or venom and LPS, showed an increase in CD86 and iNOS expression. Significantly, vTs treatment presented a response pattern similar or superior to that showed by M1 macrophages, in all evaluated parameters. Thus, our data allow us to affirm that T. serrulatus scorpion venom can activate RAW 264.7 macrophages. Furthermore, we suggest that treatment with T. serrulatus venom induces polarization for a M1 response profile.